MOLECULAR MECHANISMS AND NEUROPATHIC PAIN OCUURING DUE TO DIABETIC CONDITION - Singh, Gursimranpreet; Dhir, Ankit; Bhardwaj, Manveen; machhan, Neha; Budhiraja, R. D.; Sharma, Saurabh (Asian Journal of Pharmaceutical Research and Development, 2013)
This review is focussed on the various pathways which are involved in the neuropathic pain which mainly arises due to diabetic condition, like Polyol pathway, AGE pathway, hexosamine pathway etc. also the various mediators of pain are discussed understanding of which is useful in detailed study of neuropathic pain, like interleukins, cytokines, macrophages etc. All these processes involved lead to the painful neuropathic condition.